EFFECT OF DIATOMEAOUS EARTH TREATMENT USING HYDROGEN CHLORIDE AND SULFURIC ACID ON KINETICS OF CADMIUM(II) ADSORPTION - Nuryono Nuryono; Narsito Narsito (Indonesian Journal of Chemistry, 2002)
In this research, treatment of diatomaceous earth, Sangiran, Central Java using hydrogen chloride (HCl) and sulfuric acid (H2SO4) on kinetics of Cd(II) adsorption in aqueous solution has been carried out. The work was conducted by mixing an amount of grounded diatomaceous earth (200 mesh in size) with HCl or H2SO4 solution in various concentrations for two hours at temperature range of 100 - 150oC. The mixture was then filtered and washed with water until the filtrate pH is approximately 7 and then the residue was dried for four hours at a temperature of 70oC. The product was used as an adsorbent to adsorb Cd(II) in aqueous solution with various concentrations. The Cd(II) adsorbed was determined by analyzing the rest of Cd(II) in the solution using atomic absorption spectrophotometry. The effect of treatment was evaluated from kinetic parameter of adsorption rate constant calculated based on the simple kinetic model. Results showed  that before equilibrium condition reached, adsorpstion of Cd(II) occurred through two steps, i.e. a step tends to follow a reaction of irreversible first order  (step I) followed by reaction of reversible first order (step II). Treatment with acids, either hydrogen chloride or sulfuric acid, decreased adsorption rate constant for the step I from 15.2/min to a range of 6.4 - 9.4/min.  However, increasing concentration of acid (in a range of concentration investigated) did not give significant and constant change of adsorption rate constant. For step II process,  adsorption involved physical interaction with the sufficient low adsorption energy (in a range of 311.3 - 1001 J/mol).